Răspuns :
Răspuns:
Explicație pas cu pas:
a)
x + 3 = 1
x = 1 - 3 = - 2
b)
x - 4 = - 2
x = - 2 + 4 = 2
c)
- 2x + 1 = 5
- 2x = 5 - 1
- 2x = 4
x = 4 : (- 2) = - 2
d)
2x + 1 = - x - 5
2x + x = - 5 - 1
3x = - 6
x = - 6 : 3 = - 2
1)
a. x+3=1
x=1-3
x=-2
b. x-4=-2
x=-2+4
x=2
c. -2x+1=5
-2x=4
x=4:(-2)
x=-2
d. 2x+1=-x-5
2x+x=-5-1
3x=-6
x=-2
2)
a. x=2
b. x=-1
c. x=2
d. x=-3
Sper ca te-am ajutat!✨
a. x+3=1
x=1-3
x=-2
b. x-4=-2
x=-2+4
x=2
c. -2x+1=5
-2x=4
x=4:(-2)
x=-2
d. 2x+1=-x-5
2x+x=-5-1
3x=-6
x=-2
2)
a. x=2
b. x=-1
c. x=2
d. x=-3
Sper ca te-am ajutat!✨